2006
DOI: 10.1007/s11103-006-0036-5
|View full text |Cite
|
Sign up to set email alerts
|

Germin-like genes are expressed during somatic embryogenesis and early development of conifers

Abstract: Germins and germin-like proteins (GLPs) are members of a superfamily of proteins widely distributed in plants. Their localization within the extracellular matrix and in some cases their hydrogen peroxide-producing activity suggests that these proteins are involved in cell wall metabolism during stress responses and developmental processes. Several very highly conserved conifer GLPs have been identified in somatic embryo tissues. In order to gain more knowledge on their potential involvement in the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 54 publications
1
37
0
2
Order By: Relevance
“…The role of GLPs in enhancing somatic embryogenesis has been reported in Pinus caribaea (Domon et al 1995) and Pinus radiata (Bishop-Hurley et al 2003). Mathieu et al (2006) has reported that a GLP played a key role in somatic embryo formation in hybrid larch possibly through regulation of cell wall remodeling, which was essential for correct embryo development. Expression of ECPs have been reported to be regulated by ABA-inducible genes during acquisition of embryogenic competence (Kiyosue et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The role of GLPs in enhancing somatic embryogenesis has been reported in Pinus caribaea (Domon et al 1995) and Pinus radiata (Bishop-Hurley et al 2003). Mathieu et al (2006) has reported that a GLP played a key role in somatic embryo formation in hybrid larch possibly through regulation of cell wall remodeling, which was essential for correct embryo development. Expression of ECPs have been reported to be regulated by ABA-inducible genes during acquisition of embryogenic competence (Kiyosue et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Transcript study revealed that PcGER1 was abundant in all the embryonic lines but absent from the nonembryogenic lines whereas the PcGER1 specific transcript was detected in the quiescent zygotic embryos but not detectable in the female gametophyte and the haploid storage tissue (Neutelings et al 1998). Similarly, a small number of GLPs were found to have high transcript level expression in embryogenic tissues but no expression in nonembryogenic tissues such as roots, shoots, needles, and callus tissue in Pinus radiata (Bishop-Hurley et al 2003) and in other conifers (Mathieu et al 2006). A very recent study on Pinus pinaster identified germin-like protein and ubiquitin-protein ligase as a probable marker for somatic embryogenesis cultured on high gellan gum concentration (Morel et al 2014).…”
Section: Glp Expression At Early Developmental Stagesmentioning
confidence: 99%
“…Biochemical activity of cell wall enzymes such as b-1,3-glucanases in chicory (Helleboid et al 1998;2000), cell wall and membrane associated proteoglycan proteins such as glucosamine-and acetylated glucosamine-containing arabinogalactan proteins in carrot (van Hengel et al 2001), abscisic acid (ABA) inducible expression of embryo-specific globulin protein in maize (Duncan et al 2003), and germin-like proteins in conifer cultures (Mathieu et al 2006) are found to be associated with somatic embryo induction. Recently, a mutant Arabidopsis was identified with an inability to regenerate shoots in in vitro culture, attributed to a defect in fasciclin-like arabinogalactan protein expression (Johnson et al 2011).…”
Section: Structural Proteins and Enzymesmentioning
confidence: 99%